Dapagliflozin-Associated Euglycemic Diabetic Ketoacidosis in a Patient Who Underwent Surgery for Pancreatic Carcinoma: A Case Report - Luo, Xiaoqian; Ji, Ran; Lu, Weina; Zhu, Hong; Li, Libin; Hu, Jun (Frontiers in Surgery, 2022)
Diabetic ketoacidosis (DKA), an acute and life-threatening complication of diabetes, is a metabolic disorder caused by insulin deficiency and an increase in the counter-regulatory hormones. Several cases of DKA have been reported without marked hyperglycaemia and are defined as euglycemic DKA(eu-DKA).The use of sodium-glucose co-transporter 2 inhibitors (SGLT2is) is associated with the occurrence of eu-DKA, of which dapagliflozin is one of the agents. In this study, we report a case of dapagliflozin-associated eu-DKA following surgery for pancreatic carcinoma. A 57-year-old woman presented with acute abdomen after surgery for pancreatic carcinoma. Emergency exploratory laparotomy was performed due to suspicion of gastrointestinal perforation according to CT scan. The surgeons observed that the stomach was significantly dilated but not perforated. Meanwhile, the patient had developed shock and severe acidosis. Further examination confirmed the diagnosis of dapagliflozin-associated eu-DKA. We reviewed the precipitating factors and mechanism of SGLT2i-associated eu-DKA and discussed the treatment and prevention of this condition. Clinicians need to be alert to the occurrence of SGLT2i-associated eu-DKA in patients treated with this drug in the perioperative period.